The Service of the Community Learning in Organizing Non-Formal Education for the Development of Village Community Potential - Ainul Hayat; Zumrotun Nisaa Ul-Jannah; Dwi Eristi; Corrienna Abdul Talib (Journal of Nonformal Education, 2026)
Background - In Indonesia, many people do not have adequate access to formal education due to economic, geographical, and socio-cultural factors. This situation has resulted in low levels of education and limited opportunities for people to develop their potential. Non-formal education offers a solution to this problem through services based on local needs that empower individuals and communities. Research Urgency - Limited access to formal education requires alternative educational institutions that can reach marginalized communities, especially in rural areas. PKBM is one of the institutions that plays a strategic role in improving the quality of human resources through equivalency education and skills training. Research  Objectives - This study aims to describe the role of PKBM Aswaja in expanding access to education and empowering communities through equivalency programs and skills training tailored to local needs. Research Method - This study uses a descriptive method with a qualitative approach through observation, interviews, and documentation. Informants consist of three PKBM Aswaja administrators and two students. Results Findings - The results show that PKBM Aswaja plays a significant role in improving access to education for people who cannot attend formal education. In addition to providing Package A, B, and C equivalency programs, PKBM Aswaja also offers various skills education, courses, and vocational training according to the needs of the village community. Research Conclusion - PKBM Aswaja functions as an alternative education and empowerment center that encourages the development of community potential through flexible and locally-based educational services. Research Novelty - This study confirms that the role of PKBM is not only as a provider of equivalency education, but also as a center for rural community empowerment that integrates skills education adaptively according to the real needs of the community.